IMMUNOMODULATING THERAPY IN CHILDREN WITH ACUTE OBSTRUCTIVE BRONCHITIS - Sh.M. Ibatova,; F. Kh. Mamatkulova,; F. P. Abdurasulov, (EPRA International Journal of Research and Development (IJRD), 2022)
Currently, acute obstructive bronchitis is widespread among children in the Republic of Uzbekistan, accompanied by frequent relapses of the disease and severe complications, and occupies one of the leading places in the structure of childhood morbidity and mortality. With this pathology, the index of the T-link of the immune status changes, which leads to frequent intercurrent diseases and allergic manifestations. 65 children with acute obstructive bronchitis and 20 healthy children were examined. Children with acute obstructive bronchitis were aged from 6 months. up to 3 years. The number of T-lymphocytes (CD3), T-helpers (CD4), T-suppressors (CD8), as well as B-lymphocytes (CD19), the concentration of serum immunoglobulins A, M, G in peripheral blood were determined. Analysis of family and hereditary anamnesis, which showed that 32% of sick children were born from related marriages, in 46.5% of children, relatives suffered from allergic diseases. The phagocytic activity of neutrophils (FAN) in the acute period of the disease is significantly inhibited in children with acute obstructive bronchitis. A particularly pronounced decrease in the phagocytic activity of neutrophils was observed in children with relapses (3-4 times a year) of acute obstructive bronchitis. In order to correct immunological parameters, patients were prescribed T-activin subcutaneously at the rate of 2 μg/kg of body weight daily for 5 days and the sixth injection a week after the injections. In clinical terms, all children who received T-activin showed positive dynamics. The inclusion of T-activin in the complex therapy of children with acute obstructive bronchitis increases the effectiveness of treatment, contributes to the normalization of the immune status and prevents the development of relapses of the disease.